Antral contractility following Asian-style meal in healthy volunteers: effect of genders, menstruation, smoking status and age. - Janyarut Srijumruen; Sira Vachatimanont; Usanee Techavijit; Tawatchai Chaiwatanarat (Asia Oceania Journal of Nuclear Medicine and Biology, 2022)
Objective(s):The normal range of the frequency of antral contractions, similar to other gastric motility parameters, are different depending on the population and the test meal. We, therefore, conducted the analysis to establish the normal ranges for the frequency of antral contractions derived from dynamic antral scintigraphy (DAS) following an Asian-styled solid meal in Thai healthy volunteers.Methods:We retrospectively analyzed the data from the study on normal gastric emptying values. The dynamic scintigraphic images had been obtained in a 45 degree left anterior oblique view during the first 32 minutes following the ingestion of a 267-kcal steamed rice, a technetium-99m-labeled microwaved egg and 100 mL of water. A polynomial normalization model was used to analyze and to calculate the frequency of antral contractions. The data analysis was repeated by the same operator 1 month apart to assess reproducibility.Results:Data of 18 volunteers (10 males and 8 females) were eligible for analysis. The mean±SD of the frequencies of the antral contractions were 3.06±1.08 cycles/min on the first and 3.04±1.10 cycles/min on the second analysis. Comparison of the two analyses revealed a moderate agreement (ICC=0.632, 95% CI 0.329-0.818) without significant difference (p-value=0.942). No significant effect of gender, menstruation status, smoking or age was demonstrated in this study.Conclusion:DAS is a non-invasive technique that can measure the frequency of antral contractions. The technique is reproducible and consistent. Future study may be required to assess the effect of gender, menstruation status, smoking and age.